ANALISA FAKTOR YANG MEMPENGARUHI KINERJA PERAWAT - Sety, La Ode Muhamad; Kadir, Abd; Azuma, Anindita Paramastuti; Putra, Ryryn Suryaman Prana; Wirda, Wirda (Ensiklopedia of Journal, 2024)
Abstract: Based on the results of the initial survey conducted, it was noted that the total number of nurses working at the Makassar Hajj Hospital reached 316 people. Although the number of nurses is quite large, there are several problems that affect their performance at the hospital. One of the main problems found was the lack of motivation provided by the hospital management. Support and encouragement from the leadership is needed to improve nurses' morale, but this is still not given enough attention. The purpose of the study was to determine the factors that affect nurses' performance. The research design used in this study was cross sectional. The research was conducted at Hajj Hospital Makassar. The research was conducted in April 2022. The study population was all nurses who were in the wards of the Makassar Hajj Hospital. The research sample amounted to 36 people. The sampling technique used Simple random sampling. Data analysis was performed univariate and bivariate. The results showed there was a relationship between work motivation and nurse performance (p value: 0.001) and there was no relationship between leadership style and nurse performance. It is recommended for hospitals to improve the performance of nurses by carrying out supervision and to nurses in the form of monitoring and evaluation of every activity of providing nursing care to patients and providing opportunities for nurses to attend nursing training so that the quality of nursing services becomes better.Keywords: Performance, Motivation, Nurses.